Clinical and radiographic factors associated with the severity of paraspinal fatty infiltration in patients with degenerative low back disease - Ruiz-Treviño, A S; Miranda-González, A; García-González, O G; Martínez-Pérez, R; González Ramírez, G J; Hernández Sepúlveda, E U (Acta ortopédica mexicana, 2023)
Degenerative lumbar disease (DLE) is a spectrum of pathological changes from disc degeneration, herniated disc, spondylolisthesis and lumbar canal stenosis. The pain associated with it is multifactorial. Muscle cramps are among the most frequent causes. The relationship between muscle degeneration and DLE has already been studied in the past in multiple studies, highlighting the one carried out by Kjaer & cols. to determine the prevalence and severity of fatty degeneration in mutifidus spinae, and to study its relationship with clinical and radiographic factors. observational and analytical study. Patients diagnosed with: herniated disc, lumbar canal stenosis or degenerative scoliosis were included. They were classified according to the Kjaer scale for paraspinal fatty infiltration in one of three groups. Clinical variables were analyzed: age, smoking, obesity, the presence of axial pain, temporality of pain, severity expressed with a visual analog scale (VAS); and radiographic: number of diseased segments, involved segments, diagnostic imaging and the presence of spondylolisthesis. 56 patients with an average age of 52.5 years (16 to 80) with a predominance of females with 62.5% were included. The diagnoses were nonspecific low back pain (1.8%), herniated disc (42.9%), narrow lumbar duct (46.4%) and lumbar duct with degenerative scoliosis deformity (8.9%). The distribution among the three groups described by Kjaer was as follows: 44.6% were classified with a fat infiltration score of 2. In groups 1 and 0, 39.3% and 16.1% were classified respectively. The variables significantly related to greater fat infiltration were: age > 60 years, diagnoses of lumbar canal stenosis and herniated disc; obesity, spondylolisthesis < 2 vertebral segments involved. Axial pain and VAS > 8 points were not related to greater muscle degeneration. fatty infiltration is present in all patients with some of the forms of DLE. Most patients > 60 years of age with advanced degenerative processes have a greater severity of infiltration. Other related variables are: obesity, spondylolisthesis and disease of < 2 vertebral segments. There is no relationship between a higher percentage of fatty infiltration and axial pain or higher VAS scores.